2010
DOI: 10.3109/00207450903279717
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin, Syncoilin, and β-Synemin mRNA Levels in Dystrophic Muscles

Abstract: Progressive muscular dystrophies are genetic diseases with various modes of transmission. Duchenne muscular dystrophy (DMD) is caused by the defect of dystrophin, and Fukuyama congenital muscular dystrophy (FCMD) is caused by an abnormal fukutin gene leading to the glycosylation defect of alpha-dystroglycan. Dystrobrevin is one member of the dystrophin glycoprotein complex and its binding partners include dysbindin, syncoilin, and beta-synemin (desmuslin). Dysbindin is reported to be upregulated at the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, SNPs in this gene have been extensively associated with schizophrenia [21-23]. In vitro studies indicated dysbindin as a binding partner of several proteins with a suggested role in muscular physiology [24-26], and increased dysbindin transcript and protein levels were measured in muscle biopsies from individuals and mice with Duchenne Muscular Dystrophy (DMD; MIM 310200)  [27,28]. However, muscle pathology was not reported in mutant Dtnbp1 mice [16], and not detected in BLOC-1-deficient mice [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SNPs in this gene have been extensively associated with schizophrenia [21-23]. In vitro studies indicated dysbindin as a binding partner of several proteins with a suggested role in muscular physiology [24-26], and increased dysbindin transcript and protein levels were measured in muscle biopsies from individuals and mice with Duchenne Muscular Dystrophy (DMD; MIM 310200)  [27,28]. However, muscle pathology was not reported in mutant Dtnbp1 mice [16], and not detected in BLOC-1-deficient mice [29].…”
Section: Discussionmentioning
confidence: 99%
“…Third, elevated dysbindin is a common pathogenic factor in both the DMD (and BMD) and LGMD2H contexts [ 58 , 87 , 151 , 152 , 153 ]. Knockdown of TRIM32 in C2C12 myoblasts using siRNA resulted in elevated levels of dysbindin [ 58 ].…”
Section: Trim32 and Dmdmentioning
confidence: 99%
“…Dysbindin is a member of the dystrophin-associated protein complex, and the dysbindin level was increased in the TA muscle of mdx mice [ 151 ]. Upregulation of dysbindin expression at the mRNA level was observed in muscle biopsy samples from DMD patients compared with samples from healthy individuals [ 152 ]. In biopsy samples of the femoral quadriceps muscle from patients with DMD or BMD, TRIM32 expression was downregulated in necrotic muscle fibers compared with regenerating muscle fibers [ 153 ].…”
Section: Trim32 and Dmdmentioning
confidence: 99%